PERLINDUNGAN ANAK TERHADAP AKSESIBILITAS INTERNET BERDASARKAN UNDANG-UNDANG NOMOR UNDANG-UNDANG REPUBLIK INDONESIA NOMOR 27 TAHUN 2022 TENTANG PELINDUNGAN DATA PRIBADI - Wikutomo, Prakoso; Hamsyah Permana, Fauzan; Hari Perdhana, Muhammad (LPPM, Universitas Muhammadiyah Riau, 2025)
This study examines the protection of children’s personal data in the context of internet accessibility based on Law Number 27 of 2022 on Personal Data Protection (UU PDP). The main issues discussed are the absence of a clear legal definition of children's data and the lack of specific provisions regarding the form of parental consent in data processing. This normative legal research employs a descriptive-analytical approach by examining legislation and comparing it with the European Union’s regulations, particularly the General Data Protection Regulation (GDPR) and the UK Children’s Code. The results indicate that the Indonesian PDP Law provides insufficient protection for children due to its abstract nature and the absence of implementing technical guidelines. In contrast, the GDPR offers a comprehensive regulatory framework that centers on the best interests of the child. Therefore, it is necessary to reformulate national policy to explicitly address children’s digital rights and establish a verifiable consent mechanism that is legally enforceable.